Ta’ṡīru Istikhdāmi Wasā’iṭi YouTube fī Dāfi’i Ihtimāmi li Ta’līmi al Lughati al ‘Arabiyyati bi al Madrasati al Ṡānawiyyati al Ikhlāṣi al Islāmiyyati Jāmbī - Solehati, Lia; Prihartini, Yogia (Al-Uslub: Journal of Arabic Linguistic and Literature, 2022)
Abstract:The objectives of this research are: a) to find out how big the influence of learning Arabic by using YouTube media is. b) to find out how big the influence of learning Arabic without using YouTube media is. c) to find out whether there is an effect of learning Arabic using YouTube media on the interest of students at SMP Al-Ikhlas Jambi City. This research is a quantitative research with the type of experimental research with Post test Only Control Design. Calibration of the instruments used are Validity Test, Reability Test, Difficulty Level, Distinctive Power. Data analysis methods used are: Normality Test, Homogeneity Test, Hypothesis Testing (T-Test / Independent Sample T-Test) and Effect Size. The subjects are class VIII A students with a total of 19 as the experimental class and class VIII B with a total of 19 as the control class. Based on the results of research data analysis, it is known that learning Arabic using YouTube media on the questionnaire (questionnaire) got the highest score of 99.00, the lowest was 62.00, the average value was 80.95 and the test results got the highest score, namely 100 , the lowest is 40 , the average value is 85.25 . and learning Arabic without using youtube media and the results of the questionnaire (questionnaire) got the highest score of 92.00, the lowest was 60.00, the average value was 73.63 and the test results got the highest score of 100, the lowest was 40, the average score -the average is 66.84. So it is proven that learning Arabic using youtube media is higher than learning Arabic without using youtube media. 0.033 <0.05 and the test results obtained a 2-tailed value <0.05, namely 0.00 <0.05 then Ha is accepted, meaning that there is a significant difference between students' interest in learning Arabic by using YouTube media and interest in learning Arabic. Arabic students without using YouTube media. Meanwhile, based on the Effect Size Test, the results of the questionnaire (questionnaire) obtained a value of 0.941 with an effect percentage of 82% and on the test questions obtained a value of 0.717 with a percentage effect of 76% which means that the use of YouTube media has a high influence on the interest in learning Arabic for students in junior high school. Al-Ikhlas Jambi city.